Control of cartels and monopolies : an international comparison - Edwards, Corwin D. (Dobbs Ferry, N.Y. : Oceana Publications, 1967)
This is published under the auspices of the Institute of Comparative Law, New York University School of Law.
Includes bibliographical footnotes and index.
lje 25/01/2019
Loans
Keywords: Restraint of trade; Antitrust law